A determinação dos pontos notáveis de um triângulo utilizando o software GeoGebra - Felício, Adriano César (Universidade Federal de São Carlos, 2013)
In this paper, I intend to report the experience of implementing an activity in some classes in a public school of the city of Ribeirão Preto, state of São Paulo, where it was made an approach to the subject "Notable Points of a Triangle" by using the software GeoGebra like as a tool for teaching and learning. The aim is to analyze students' reactions and the interaction of the same at the presentation of the content using this software. Also a comparison of the progress is made with regard to student learning through the production and execution of activities, consisting of scripts/walkthroughs. The methodology used is the didactic engineering. Working in pairs, due to the limited amount of computers in the computer lab of the school, improved academic relations between some students, arising naturally an exchange of ideas and awakening a spirit of collaboration in a very healthy learning space. At the end of the study the author concluded that activities using computing resources as an educational tool optimizes the process of teaching and learning.
Keywords: Matemática - estudo e ensino; Triângulo; Baricentro; Incentro; Circuncentro; GeoGebra (Software de computador); Pontos notáveis de um triângulo; Ortocentro; Notable points of a triangle; Barycenter; Incenter; Circumcenter; Orthocenter; CIENCIAS EXATAS E DA TERRA::MATEMATICA